2010
DOI: 10.3928/01484834-20091118-02
|View full text |Cite
|
Sign up to set email alerts
|

The Professional Practice Knowledge of Nurse Preceptors

Abstract: Significant research has been conducted and disseminated on preceptorship as an essential component in teaching and evaluating student learning in the final clinical practicum. The preceptorship triad-formally defined as an equilateral relationship among a nurse preceptor, faculty member, and undergraduate nursing student-overlooks the contextual challenges preceptors encounter. Preceptors develop relationships in the clinical setting to enhance teaching, and more importantly, to ensure student practice reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 18 publications
2
22
1
2
Order By: Relevance
“…It has been suggested that if students are educated and advised in advance on what to expect during PEP, they can be more observant of SWN behaviours and attitudes (Felstead, 2013). This can lead to an improvement in the expectations of the relationship between the student and the SWN with the mutual understanding that the patients' needs come first (Paton, 2010). The findings also reinforce the importance of a positive learning culture facilitated by the SWN's within the clinical environment and the influence this has on student learning.…”
Section: Discussionmentioning
confidence: 95%
“…It has been suggested that if students are educated and advised in advance on what to expect during PEP, they can be more observant of SWN behaviours and attitudes (Felstead, 2013). This can lead to an improvement in the expectations of the relationship between the student and the SWN with the mutual understanding that the patients' needs come first (Paton, 2010). The findings also reinforce the importance of a positive learning culture facilitated by the SWN's within the clinical environment and the influence this has on student learning.…”
Section: Discussionmentioning
confidence: 95%
“…La literatura demuestra que el proceso de aprendizaje clínico será exitoso si los estudiantes reportan una variedad de oportunidades de aprendizaje que les motiva y les anima a realizar análisis crítico de las experiencias, pero sin aumentar desmesuradamente y sin justificación la carga de trabajo de los estudiantes (9,43,44) . En cuanto a la "supervisión clínica", aunque existe una variedad de modelos de supervisión de los estudiantes de enfermería empleados en los países europeos, numerosos autores coinciden al considerar a la enfermera tutora como la figura clave en el proceso de la supervisión clínica (9,21,41,42,44,45) . Además, la relación estudianteenfermera tutor parece ser decisiva para el aprendizaje del alumnado, tanto epistemológica como ontológicamente (43) .…”
Section: Discussionunclassified
“…Not only is it optimal for nursing staff to be formally trained as preceptors, it is widely supported in the literature that preceptors require the support of their coworkers, nurse educators, and the organization (Kaviani & Stillwell, 2000). And while preceptor expertise and knowledge are undoubtedly essential to a successful preceptorial relationship, other aspects such as the ability to self-reflect on performance, be honest, organized, objectively evaluate performance, and demonstrate a genuine concern for the preceptee have been identified as equally important (Boyer, 2008;Myrick & Barrett, 1994;Patton, 2010).…”
Section: Literature Reviewmentioning
confidence: 97%